IDENTIFIKASI DAMPAK PEMBANGUNAN KEK MANDALIKA TERHADAP KONDISI EKONOMI WILAYAH PENYANGGANYA - Aini Rachmawati, Nur
Tourism has taken an important role in economic and regional development. To optimize these potency, it is necessary to develop tourism. One of Indonesia’s tourism development programs is the construction of Mandalika which is a Special Economic Zone (SEZ), National Tourism Strategic Area and super priority tourism destination. Tourism development always has an impact on the tourism destination itself and its surrounding areas, including economic impact. One of the areas that will be affected by the development of Mandalika SEZ is its buffer zone. Therefore, this study aims to identify the economic impact of Mandalika SEZ development to its buffer zone, both on the village and the people who live in it. Variables used to study the economic impact of the village consist of basic infrastructure and tourism amenities; local industries and products; prices of food and land; and village income. Variables used to assess the economy of people living in the buffer zones are their livelihood and income. This is a descriptive research conducted using a mixed-method approach with three methods of analysis, those are descriptive statistical analysis; inferential statistical analysis with three test methods: Chi-Square test, Mann-Whitney test, and Wilcoxon test; and descriptive qualitative analysis. Based on the analysis, discovered that the development of Mandalika SEZ gives positive impacts to the improvement of basic infrastructure and tourism amenities; increasing the number of industries, variation, and demand of local products; improving village income; creating job, employing local workers, reducing unemployment; and generating more income for people working in the tourism sector. On the other hand the development of Mandalika SEZ also has negative impacts by increasing food and land price, creating local inflation of land; and increasing public dependency towards tourism.